The Quality of Geography Textbook of Twelve-Grade and Their Implications for The Development of Students Geographic Thinking Skills - Ambarwati, Pragita Dyah; Maryani, Enok; Yani, Ahmad (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2021)
Geography textbooks are one of the best sources for supporting geographic skills development. Geography textbooks contain not only content knowledge, but also geography textbooks that should contribute to the development of geographic thinking skills. Quality textbooks can develop students' critical thinking skills. But in reality, students' geographical thinking skills are very low. This study has the purpose of, (1) analyzing the quality of the presentation of material in the high school geography textbook in developing students' geographic thinking skills, (2) identifying the achievement of skill development indicators and geographic thinking in the geographic textbooks used. The method used in this study is literature studies, in which the geographic textbooks used will be selected through the survey stage. The result of this research is to develop textbook analysis techniques for developing geographic thinking skills. The table used is a table that has never been tested because it is the result of a literature study only.